Neutralization activity of influenza A virus humanized antibodies against new subtypes of influenza viruses - Jing Liu; Tiecheng Wang; Ying Xie; Yuanguo Li; Jian He; Xinghai Zhang; Weiyang Sun; Na Feng; Chuan Qin; Yuwei Gao; Xianzhu Xia (Elsevier, 2019)
Antibodies are ideal for controlling the influenza A virus, but their effect on newly emerging strains is unclear. Here, we assessed the neutralization activity of the humanized monoclonal antibodies (mAbs) F10, H98 and H40 against circulating influenza viruses (H5N1, H1N1, H3N2 and H7N7 and new subtypes viruses H5N6 and H7N9). The results showed that all the three humanized mAbs (F10, H98 and H40) displayed different degrees of virus neutralization activities when encountered with different subtypes of influenza viruses. Remarkably, the humanized monoclonal antibody F10 produced higher and broader neutralization titers (range 25-1.56 μg/ml) than those of the other two humanized mAbs (H98 (range 50-3.12 μg/ml), H40 (range 50-5.56 μg/ml)) to against the viruses H5N1, H1N1, H3N2, H7N7, H5N6 and H7N9. This mAb may represent a new class of heterosubtypic neutralizing humanized mAb that could replace vaccines and chemical drugs.